Geochemical Signatures of Volcanic Rocks Related to Gold Mineralization: a case of volcanic rocks in Pasaman area, West Sumatera, Indonesia - Iskandar Zulkarnain (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2005)
Gold deposit is always related to volcanic activities. They occur usually in areas characterized by multi magmatic activities, indicated by occurrences various volcanic rocks with wide range composition. The source of the gold metal is believed to be magma, but not all magmatic activity related to gold mineralization. However, among different volcanic rocks in a multi magmatic activities area, only a certain magmatic or volcanic activity that related to the mineralization while the other products should be classified as barren type. It should give an important contribution for mining exploration in effort to discover new deposits in the future, if the volcanic rocks related to mineralization can be recognized easily and separated from the barren ones.Pasaman area located in west flank of Bukit Barisan Mountain within West Sumatera Province is reported since Japanese time to nowadays having indications of gold mineralization. Small scale mining by the local people was running in Tambang Pambaluan and area near Simpang Dingin in Dua Koto Sub-District during Japanese time, but now is not active anymore. At Bonjol, in Bonjol Sub-District, local people are still doing mining activity using amalgamation method and this activity has been running for a few decades since the Dutch time. The locations are situated in a wide area that covered by so called undifferentiated volcanic rocks without any trace of its eruption center. Major elements have been failed to separate volcanic rocks related to mineralization from the barren ones, but trace elements and REE signatures can be used effectively for the purpose. Analytical data of the rocks collected from the undifferentiated volcanic area show clear and different character of the rocks related to mineralization compared to the barren ones. The rocks related to mineralization contain Ytrium less than 10 ppm, while the barren rocks have more than 20 ppm Ytrium content. Furthermore, the rocks related to mineralization are slightly enriched on Rb. More specific character for the rocks related to mineralization is observed on REE diagrams. REE pattern of the rocks related to mineralization shows a clear and significant depletion on medium to HREE (from Gd to Lu), although the depletion can be recognized from Sm and Eu elements. The specific geochemical signatures of the rocks are interpreted to be caused by the presence of gold metal in the magma. The aim of this paper is to demonstrate that the rocks related to mineralization have specific geochemical signatures and different from the barren rocks. The specific signatures have been found out through comparison of trace elements and REE pattern between rocks related to mineralization collected from Tambang Pambaluan, Simpang Dingin dan Bonjol with the barren rocks collected in other locations in the undifferentiated volcanic area in Pasaman